Aetiology and outcome of generalized convulsive status epilepticus in elderly. (July 2015) - Jayalakshmi, Sita; Vooturi, Sudhindra; Chepuru, Ramesh; Sahu, Sambit; Surath, Mohandas
Highlights: Acute symptomatic aetiology was the commonest cause of SE (60.6%) in elderly. Vascular aetiology was not associated with progression to RSE or mortality. Nine (27.3%) patients progressed to RSE of which five patients had prolonged RSE. The overall mortality was 18.2%. Abstract: Purpose: Convulsive status epilepticus (CSE) is a common neurologic emergency in elderly people. The current study elaborates the clinical characteristics and outcome of CSE in elderly patients. Methods: Analysis of data of generalized CSE patients, aged 60 years and above admitted at the neurointensive care unit (NICU) was performed. The primary outcome for analysis was in-hospital mortality. The study population was divided into groups based on progression of CSE and mortality to analyze difference in study variables. Mortality of the group was analyzed using life tables. Results: A total of 33 patients satisfied the inclusion criteria from medical records of 212 patients with CSE. Mean age of the study population was 67.0 ± 6.8 years; 69.7% were men. Acute symptomatic aetiology was the commonest cause of CSE (60.6%); nine (27.3%) patients progressed to refractory status epilepticus (RSE) of which five patients had prolonged RSE. The overall mortality was 18.2%. Complications of mechanical ventilation and mean age were higher in patients who died. Though vascular aetiology was the leading cause of CSE (39.3%), it was not associated with progression to RSE or mortality. Acute symptomatic aetiology accounted for five out of the six deaths in the entire cohort. Conclusion: Less than one-third of elderly patients with CSE progressed to RSE. Vascular aetiology, the leading cause of generalized CSE in elderly, was not associated with progression to RSE and mortality. Acute symptomatic aetiology was associated with high mortality.